International Integration of Pharmaceutical Supply Chains in Vietnam: An Overview of Challenges and Opportunities at Hospitals in Ho Chi Minh City - Quan, Nguyen Huu Khanh (International Journal of Medical and Health Sciences Research, 2020)
The purpose of this paper is to analyze the changing aspects of the types of pharmaceuticals purchased, distributed, and sold throughout the supply chain in hospitals in Ho Chi Minh City. The information for analysis is based on the secondary data from the previous studies. The research was combined with analysis from practitioner papers to gain key insights change affects the international integration of pharmaceutical supply chains in hospitals in Ho Chi Minh City. The outcomes of the study are suggestions four key issues: Pharmacists are a workforce of hospital workers to provide quality products and services at affordable prices; Quality management is an important component of all hospital or healthcare industry; Hospitals ensure patient supply continuity is to protect the brand and the hospital by restoring normal operations as quickly as possible with minimal disruption; Hospitals need to pay attention to applying the techniques and information technology available today to build integrated relationships from stakeholders in the supply chain to create a competitive advantage, using comprehension. Information technology results play a very important role in the success of the hospital. The hospital wanted to get the pharmaceutical supply chain's desired performance measurable by monitoring and controlling its operation. The article contributes specific information about the pharmaceutical supply chain in hospitals in globalization for Vietnam.